2021
DOI: 10.21203/rs.3.rs-847319/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Study on intestinal flora of acupoint catgut embedding intervention in female patients with abdominal obesity: Study protocol for a randomized controlled trial

Abstract: Background With high morbidity, and many complications, obesity has become a global public health problem, and attracted extensive attention from the medical community. Previous studies have suggested that acupoint catgut embedding (ACE) is a safe and effective therapy for abdominal obesity (AO). However, the investigation of its mechanisms remains limited. The purpose of this study is to observe the effect of ACE intervention in AO on the intestinal flora, to reveal its site of action and therapeutic mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 26 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…Total effective rate. Twenty-nine studies [14,22,27,29,31,32,34,37,44,[48][49][50][51][56][57][58][60][61][62]64,69,72,73,76,84,85,[88][89][90] out of 30 including 2100 participants (1060 in the experiment group and 1040 in the comparison group) were included in the meta-analysis to synthesize the total effective rate. As shown in Figure 2A, the pooled results showed that ACE was more effective than MA (RR = 1.12 [1.07, −1.18]; P < .00001, I 2 = 45%).…”
Section: 311mentioning
confidence: 99%
See 4 more Smart Citations
“…Total effective rate. Twenty-nine studies [14,22,27,29,31,32,34,37,44,[48][49][50][51][56][57][58][60][61][62]64,69,72,73,76,84,85,[88][89][90] out of 30 including 2100 participants (1060 in the experiment group and 1040 in the comparison group) were included in the meta-analysis to synthesize the total effective rate. As shown in Figure 2A, the pooled results showed that ACE was more effective than MA (RR = 1.12 [1.07, −1.18]; P < .00001, I 2 = 45%).…”
Section: 311mentioning
confidence: 99%
“…Eighteen studies [14,22,29,34,37,44,45,[48][49][50]57,64,72,76,85,[88][89][90] assessed the benefit of ACE in reducing the BMI. However, the results showed serious heterogeneity (I 2 = 86%).…”
Section: Bmimentioning
confidence: 99%
See 3 more Smart Citations